Measurements of radon concentration in drinking water samples from Kastamonu (Turkey) - Gürler, Orhan; Akar Tarim, Ürki̇ye; Incirci, Fulya; Yalcin, Sezai; Gündoğdu, Özcan; Kaynak, Gokay (Informa UK Limited, 2011)
Concentration of (222)Rn was determined in selected natural spring and tap water samples collected during spring and summer seasons from Kastamonu, Turkey. The aim of this work was to produce a map of the radon concentrations in water sources of the province and to determine any potential radiological risk for the local population. Radon measurements were performed by an AlphaGUARD radon gas analyser. The average radon concentrations were found to vary from 0.39±0.02 to 12.73±0.39 Bq l(-1) for natural springs and from 0.36±0.04 to 9.29±0.45 Bq l(-1) for tap water in spring, from 0.50±0.09 to 19.21±1.00 Bq l(-1) for natural springs and from 0.31±0.03 to 13.14±0.38 Bq l(-1) for tap water in summer. Furthermore, the results are compared with international recommendations and concentrations reported for other countries. Doses resulting from the consumption of these waters were calculated. The effective dose equivalents due to the intake of the (222)Rn present in these waters are expected to range from 0.93 to 32.54 μSv y(-1) in summer and from 0.80 to 49.09 μSv y(-1) in spring.
Keywords: Water Pollutants, Radioactive; Turkey; Drinking Water; Radiation Dosage; Radiation Monitoring; Radon; Water Supply; Humans; 6. Clean water; 13. Climate action